Upaya Menjaga Ketangguhan Keluarga pada Suami Gamer - Muhammad Luthfi Azzam Zuhdi; Candra Indraswari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Family resilience is crucial in the family. To maintaining it, there needs to be efforts to grow, process and adapt in order to create resilience and the welfare of family relationships. In a family with a husband as a gamer, has risks and family conflicts due to a penchant for playing online games. The purpose of this study was to examine family resilience in gamer husbands. Informants were obtained through a phenomenological approach on three married couples. The results showed that two families have experienced conflict due to their husband playing games, and the other one did not experience conflict. In families that did not experience conflict, there were preventive efforts by seeking resilience resources in the midst of the risk of conflict that has the potential to occur. Families that have experienced conflict, there is an effort to grow and empower the resilience resources owned in their family. Three couples had family toughness that came from material and immaterial. One of the most prominent material findings was financial power, while the immaterial was time management, communication, and support from parents. However, three couples experience the same conflict but can be muted and did not become a prolonged conflict.